(untitled) (Web of Teachers: Inderscience Research, 2024)
Dialects can be defined as the unique variations of a language that arise from speakers in a specific geographical region, social or economic class, or ethnic group. Dialects can include differences in vocabulary, pronunciation, grammar, and syntax. These variations often exist within a common language and can sometimes result in communication barriers between speakers of different dialects. Taking all mentioned above into consideration, this research investigates the importance of the dialects and its implication in teaching English language.